Residual Effect of Tillage Options, Organic Manures and Irrigation Levels of Rice on the Productivity of Succeeding Wheat Grown under Rice-Wheat System in Mollisols of Uttarakhand - M.S. Yadav; M.S.PAL (Journal of Soil and Water Conservation, 2022)
Continuous monocropping of rice-wheat cropping system has not only declined the system productivity and soil fertility, but also exerted a strong influence on the productivity of succeeding wheat. It has been observed that the wheat productivity is lowered if grown after puddle rice. This may be because of either poor aeration or exhausted soil fertility or both, Since the rice-wheat system is the most predominant cropping system in Indo-Gangetic plains and contributes nearly 25 percent to the total food grain basket, it is essential to maintain the sustainability of this system. Hence, the field experiment was carried out during 2001-02 and 2002-03 at G. B. Pant University of Agriculture & Technology, Pantnagar to study the residual effect of tillage options, organic manures and irrigation levels of rice on the productivity of succeeding wheat crop in Mollisols of Uttaranchal. The experimental results showed significant residual effect of tillage options and organic manures on yield attributes and grain yield of wheat during both the years. The reduced tillage gave 8.2 percent higher grain yield of wheat than conventional tillage system. The Sesbania green manuring gave 2.5 and 12.9 percent higher grain yield of wheat than FYM and control treatments, respectively. Therefore, it can be concluded that the productivity of rice-wheat system can be restored by adoption of reduced tillage in rice crop combined with organic manuring, either by green manuring or by application of 10 t FYM/ha. This would also increase the productivity of succeeding wheat crop.